Risco de quedas em idosos com doença de Parkinson e demência de Alzheimer: um estudo transversal - Christofoletti, G [UNESP]; Oliani, Mm [UNESP]; Gobbi, Ltb [UNESP]; Gobbi, S [UNESP]; Stella, F [UNESP] (Associação Brasileira de Pesquisa e Pós-Graduação em Fisioterapia, 2006)
OBJECTIVE: To compare the risk of falls among elderly people with Parkinson's disease (PD) and Alzheimer's dementia (AD) and among healthy peers (controls). In addition, the aim was to analyze relationships between risk of falls and cognitive decay and between risk of falls and physical activity. METHOD: Twenty subjects were assessed: seven with PD (69.57 ± 2.40 years), six with AD (77.5 ± 2.32 years) and seven healthy peers (74.71 ± 2.58 years). The following instruments were used: Berg Balance Scale (BBS), Timed Up and Go test (TUG), Mini-Mental State Examination (MMSE) and Modified Baecke Questionnaire for Older Adults (MBQOA). RESULTS: The Kruskal-Wallis (KW) test indicated significant differences between the groups, relating to BBS (KW = 9.67, p<0.01) and TUG (KW = 9.14, p<0.01, for time expended, and KW = 10.04, p<0.01, for number of steps). Bonferroni post-hoc pairs analysis showed that balance was highly compromised in the AD group, such that lower MMSE values were observed. The PD group was characterized by presenting higher levels of physical activity. Spearman's test produced low correlations between MMSE and BBS (r s=0.59); MMSE and TUG (r s=-0.52 and r s=-0.62); MBQOA and BBS (r s=0.54); and MBQOA and TUG (r s=-0.39 and r s=-0.42). CONCLUSION: These low correlations must be analyzed carefully, because these variables are influenced by multiple factors. In the AD group, the cognitive decay can be positively associated with greater risk of falls. In the PD group, physical activity may have assisted in maintaining the risk of falls at similar levels to the control group.

OBJETIVO: Comparar o risco de quedas entre idosos com doença de Parkinson (DP), demência de Alzheimer (DA) e saudáveis (controle). Além disso, pretendeu-se analisar as relações do risco de quedas com declínio cognitivo e com nível de atividade física. MÉTODO: vinte idosos, sendo sete com DP (69,57 ± 2,40 anos), seis com DA (77,5 ± 2,32 anos) e sete saudáveis (74,71 ± 2,58 anos), foram avaliados por meio dos seguintes instrumentos: Escala de Equilíbrio Funcional de Berg (EEFB), Timed Up and Go test (TUG), Mini-Exame do Estado Mental (MEEM) e Questionário Baecke Modificado para Idosos (QBMI). RESULTADOS: O teste de Kruskal-Wallis apontou diferença significativa entre os grupos, tanto em relação à EEFB (KW=9,67, p<0,01), quanto em relação ao TUG (KW=9,14, p<0,01, para tempo despendido, e KW=10,04, p<0,01, para número de passos). A análise aos pares do teste post-hoc de Bonferroni apontou comprometimento maior do equilíbrio no grupo DA, no qual também foram observados menores valores no MEEM. O grupo DP foi caracterizado por apresentar um maior nível de atividade física. A análise de correlação de Spearman apontou correlação baixa entre MEEM e EEFB (r s=0,59); entre MEEM e TUG (r s=-0,62 e r s=-0,52); entre QBMI e EEFB (r s=0,54); e entre QBMI e TUG (r s=-0,39 e r s=-0,42). CONCLUSÕES: As baixas correlações observadas devem ser analisadas com cautela, pois tais variáveis sofrem influência de múltiplos fatores. No grupo DA, o declínio cognitivo pode estar relacionado ao maior risco de quedas e, no grupo DP, a atividade física pode ter auxiliado a manter um risco de quedas próximo ao grupo controle.
Risk of falls among elderly people with Parkinson's disease and Alzheimer's dementia: a cross-sectional study
Keywords: risk of falls; Parkinson's disease; Alzheimer's dementia; risco de quedas; doença de Parkinson; demência de Alzheimer